Voice professionals and future professionals: work environment, incorrect vocal habits and vocal complaints (Research, Society and Development, 2021)
Objective: To verify and associate the unfavorable characteristics of voice production in the workplace, incorrect vocal habits and vocal complaints from professionals and future voice professionals. Method: Cross-sectional, non-experimental, retrospective and quantitative study, using a database from a speech therapy clinic-school. Were selected 137 records from the database about voice professionals and future voice professionals, male and female, adults. The data extracted from the records related to unfavorable factors of voice production in the workplace, incorrect vocal habits and vocal complaints. The Proportion Hypothesis Test, Pearson's Chi-square Test and Fisher's Exact Test used with a 5% significance level. Results: There was a statistically significant frequency of unfavorable factors of voice production in the workplace, incorrect vocal habits and vocal complaints; there was a significant association between unfavorable factors of voice production in the workplace and incorrect vocal habits, and between unfavorable factors of voice production in the workplace and vocal complaints. Conclusion: In this group of professionals and future voice professionals, there was a high occurrence of unfavorable factors of voice production in the workplace, vocal complaints, and incorrect vocal habits, as well as an association of vocal complaints and incorrect vocal habits with unfavorable factors of voice production in the workplace. Therefore, it is noteworthy that prevention, associated with better working conditions, can result in a decrease in dysphonia in professionals and future voice professionals.